Recognising the importance of self-management for people with diabetes. Issue 7 (2nd July 2019) - Phillips, Anne
Abstract : This is an exciting time for diabetes care, as this article articulates the developments occurring and the changes that will affect the care and experience of people living with type 1 and type 2 diabetes in the UK. A key theme within care is person-centredness, and this reflects the guidance of Language Matters, which is an essential document that every health professional should be made aware of to enhance their practice. This article gives information regarding the key themes and drivers for current and future diabetes care.